Case Report: High-dose immunoglobulins prior to plasma exchange in severe pulmonary renal syndrome - Schäfer, Ann-Kathrin; Dierks, Sascha; Schnelle, Moritz; Korsten, Peter; Hakroush, Samy; Tampe, Björn (Frontiers in Immunology, 2023)
Plasma exchange rapidly depletes pathogenic anti-neutrophil cytoplasmic autoantibodies (ANCAs) and is considered for induction therapy in severe ANCA-associated vasculitis. The aim of plasma exchange is to remove putative disease mediators from the circulation, such as toxic macromolecules and pathogenic ANCAs. To our knowledge, we here provide the first report of applying high-dose IVIGs prior to plasma exchange and assessment of ANCA autoantibody elimination in a patient with severe pulmonary renal syndrome due to ANCA-associated vasculitis. After high-dose application of intravenous immunoglobulins (IVIGs) prior to plasma exchange treatment, efficacy of myeloperoxidase (MPO)-ANCA autoantibody elimination was substantially increased, associated with rapid clearance of MPO-ANCA autoantibodies. High-dose IVIGs resulted in marked reduction of MPO-ANCA autoantibody levels and did not directly affect autoantibody clearance by plasma exchange itself, as also confirmed by comparable MPO-ANCAs in the exchange fluid relative to serum levels. Moreover, measurements of serum creatinine and albuminuria confirmed that high-dose IVIGs were well tolerated and did not exacerbate kidney injury.